Does Foreign Aid Accelerate Economic Growth? An Empirical Analysis For Nigeria - Fasanya, Ismail Olaleke; Onakoya, Adegbemi B.O (International Journal of Economics and Financial Issues, 2012)
This paper analyses the impact of foreign aid on economic growth in Nigeria during the period of 1970-2010 making use of annual time series data. The empirical analysis rests on the neo-classical modelling analytical framework and combined several procedures in modern econometric analysis/estimation techniques. Our findings shows that aid flows has significant impact on economic growth in Nigeria: domestic investment increased in response to aid flows and population growth has no significant effect on aid flows. Aid flows also provides free resources to increase domestic investment, thus confirming the aid-policy-growth hypothesis. Therefore, donor governments should be aware of the political situations in recipient countries, and work with international bodies to ensure as much stability as possible. Finally, foreign aid transfers should henceforth pledge to abide by the oath to of doing no harm. Keywords: Foreign Aid; Policy; Modelling; Economic Growth; Nigeria JEL Classifications: C01; C51; E13; F35